2004
DOI: 10.1021/jf030821y
|View full text |Cite
|
Sign up to set email alerts
|

Total Recovery of the Waste of Two-Phase Olive Oil Processing:  Isolation of Added-Value Compounds

Abstract: A process for the value addition of solid waste from two-phase olive oil extraction or "alperujo" that includes a hydrothermal treatment has been suggested. In this treatment an autohydrolysis process occurs and the solid olive byproduct is partially solubilized. From this water-soluble fraction can be obtained besides the antioxidant hydroxytyrosol several other compounds of high added value. In this paper three different samples of alperujo were characterized and subjected to a hydrothermal treatment with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 19 publications
3
59
1
Order By: Relevance
“…Qualitative and quantitative characterizations of these solid and aqueous wastes suggested that these byproducts could be considered an important natural source of phenolic compounds, which, after suitable purification, could be used as food antioxidants or as ingredients in nutraceutical products due to their interesting technological and pharmaceutical properties. Fernández-Bolaños et al (2004) suggested a process for the value addition of solid waste from twophase olive oil extraction includes a hydrothermal treatment, leading to the production of different mixtures of soluble oligosaccharides. Ghanbari et al (2012) focuses on the nutrients and high-value M A N U S C R I P T…”
Section: Olivesmentioning
confidence: 99%
“…Qualitative and quantitative characterizations of these solid and aqueous wastes suggested that these byproducts could be considered an important natural source of phenolic compounds, which, after suitable purification, could be used as food antioxidants or as ingredients in nutraceutical products due to their interesting technological and pharmaceutical properties. Fernández-Bolaños et al (2004) suggested a process for the value addition of solid waste from twophase olive oil extraction includes a hydrothermal treatment, leading to the production of different mixtures of soluble oligosaccharides. Ghanbari et al (2012) focuses on the nutrients and high-value M A N U S C R I P T…”
Section: Olivesmentioning
confidence: 99%
“…However, in all cases its content was higher in solids after treatment than in the fresh date (about 4% when calculated on dry and soluble sugar-free basis). Hydrothermal treatments lead to enrichment in cellulose (among other components) in the recovered solid (Fern andez-Bolaños et al, 2004;Garrote et al, 2008). Besides, the partial hydrolysis of seeds, whose content in cellulose was higher than that of flesh (Table 1), could also contribute to the increase in the percentage of cellulose.…”
Section: Chemical Composition Of Fcsmentioning
confidence: 99%
“…Recently, Mrabet et al (2012) concluded that some of these varieties could be valuable as a source of antioxidant dietary fiber, but pre-treatment could be necessary for the total utilization of the dates. One of the more interesting processes is based on hydrothermal pretreatments that allow for the extraction of soluble compounds to the liquid phase, leaving a fibrous material as solid fraction (Fern andez-Bolaños et al, 2004). Among the existing methods, steam explosion treatment (SET) is one of the most commonly used for fractionation of biomass components.…”
Section: Introductionmentioning
confidence: 99%
“…Olive residues have been characterized as a possible source of animal feed or other valuable products [7][8][9][10][11]. Ballesteros et al [2] used waste from a two-step centrifugation process, adopted in Spain for extraction of olive oil, for ethanol fermentation.…”
Section: Introductionmentioning
confidence: 99%